Peran Hukum Internasional Guna Menjaga Keamanan Dunia (Dalam Perspektif Kedamaian Negara) - Huzeilia Ananda Nasution; Emiel Salim Siregar; Ike Nindya Mayori; Nuriani Ningsi; Dodi Muhammad Irvan Siregar; Nike Nurlina; Novi Adeltya; Daniel Khalid (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this writing is to understand the role of international law and to analyze and describe the role of international law in state peace. The approach method used in this writing is the normative juridical method, which is legal bibliography writing, namely writing on secondary data such as benchmarks in order to look for symptoms of events which are the object of writing. The type of writing used is descriptive analytical, namely writing which explains the applicable laws and regulations in connection with legal theories and implementation practices, in the end of which conclusions will be made according to the problem which is the object of writing. Based on the results, it is concluded that International Law is the part of law which regulates the activities of international organizations. The aim of international relations is to increase bilateral, regional and multilateral cooperation through many forums which are based on national interests and competencies. Even though a country's international relations are not always positive and often trigger disputes between countries, the international community is very interested in efforts to resolve them. This effort aims to improve relations between countries so that they are more harmonious based on the principles of international peace and security. This raises important questions about the role of international law in upholding justice in order to achieve world peace and security and build relations between countries based on the principles of international peace and security.